The Effectiveness of Lemon Aromatherapy on Blood Pressure in Hypertension Patients in Modopuro Public Health Center, Mojokerto - Brigita Aulia Juliana Soeryanto; Binarti Dwi W; Enny Virda Yuniarti; Ika Ainur Rofi’ah (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Hypertension is systolic blood pressure increases above 140 mmHg and diastolic blood pressure increases above 90 mmHg. One of the hypertension treatments is non-pharmacological therapy by giving lemon aromatherapy, which is helpful as an antioxidant, strengthens and vasodilation of blood vessels, and controls blood pressure. This study aimed to analyze the effectiveness of lemon aromatherapy on blood pressure in hypertension patients at Modopuro Public Health Center Mojokerto. The research design used pre-experimental with a one-group pre-post test design approach. The sample used 35 respondents with a purposive sampling technique. The research instrument used a digital tensimeter and a blood pressure observation sheet. Statistical analysis test used the Paired t-test. The results showed that the mean systolic blood pressure before intervention was 158.34 mmHg, and the mean systolic blood pressure after intervention was 144.42 mmHg. The results showed a significant difference between systolic blood pressure before and after giving lemon aromatherapy in hypertension patients (p-value = 0.000; α <0.05). Lemon aromatherapy can decrease blood pressure in hypertension patients, affecting the olfactory and circulatory nervous systems. When aromatherapy is inhaled, the olfactory nerve delivers impulses to the brain and stimulates the production of endorphins, which can calm and relax the body. That mechanism can cause vasodilation of blood vessels and a decrease in heart rate so that blood pressure will decrease. Keywords: Lemon Aromatherapy, Blood Pressure, Hypertension